Assesment of 28 days repeated adminstration toxicity profile of dexamethasone palmitate injection - Sharma, Ganesh N; Rasania, Shaili; Dadhaniya, Paresh; Patel, Chintan; Vachhani, Kapil (Journal of Nepal Pharmaceutical Association, 2015)
Although, the dexamethasone have been used for the managements, against various ailments as single API or in combination with other drugs as acetate or palmitate salt. However, Dexamethasone as palmitate salt has not been investigated so far for sub acute toxicity on intravenous administration. Therefore, an attempt has been made to investigate sub-acute toxicity of dexamethasone palmitate injection. The drug was administered in experimental animals at different dose levels (0.07, 0.18 and 0.44 mg/kg, b.w.), for 28 days, and alteration in biochemical and haematological parameters was recorded along with histological examinations. The result data revealed that intravenous administration of dexamethasone palmitate does not causes any significant alteration in experimental animals examined at different levels. The observed changes were either well established adverse effects of Dexamethasone or were in laboratory reference range limit. The intravenous administered doses of drug were found safer, although somewhat adverse reactions may be observed at higher dose level (s). DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12145 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 9-19